Feminicídio ou homicídio doloso contra a mulher?: a narrativa sociojurídica da promotoria e dos juízos das varas do Tribunal do Júri para caracterizar crimes contra a vida de mulheres na cidade do Recife. - Silva, Fábia Lopes Gomes da (2022)
Law nº 13.104/2015 – Femicide Law – is another Brazilian rule created in the midst of legislation that was born from the promise that Criminal Law would be a safe way to eradicate violence against women. However, seven years after its entry into force, it is noticeable that the novel qualifying homicide, even if it denounces the practice of misogyny in Brazil, has not been enough to curb the violent deaths of women in the context of domestic and family relationships, or in the field of the public sphere, where the perpetrators are men unknown to the victims or with whom they had little proximity. It is observed, therefore, that the regulation, by itself, cannot oppose the historical criminal legacy of patriarchy, namely: the physical elimination of women due to their sexual differentiation at birth. Thus, the academic study brings to critical reflection two historical facts of Modernity that boosted the formation of the inaugural Feminism - considering that the movement is recognized worldwide as an icon of the struggle for the end of violence against women: i) Femicide in mass (or gendercide) of white women in Western Europe (1487-1760), commonly known as the “Witch Hunt” and (ii) the denial of citizenship to women in the Republic by the French Revolution (1789- 1799). The importance of this historical retrospect is due to the fact that Feminisms, even with internal differences and still making symbolic use of punitive power, were responsible for forcing the State to create measures and services to protect women, saving thousands of them from male hatred. In this way, it is necessary to value the fact that the legislative novelty of 2015 removed the expression “crime of passion” from the Brazilian legal system, thus reaching the defense thesis, until then, used to reduce the responsibility of men accused of the practice of crime. misogynistic crime. However, the new legal text presents gaps regarding the faithful characterization of Feminicide, forcing delegates, prosecutors and judges to make efforts to identify the circumstances and conduct practiced in the execution act of the crime that denote having the woman was killed for “reasons of the female sex”. This is because not every intentional homicide committed against a woman is necessarily a femicide. In this perspective, the present academic study, of an empirical nature, analyzed the Complaints and Pronouncements of crimes against the lives of women committed in Recife between 2015 and 2020, in order to observe the arguments presented by the Public Ministry and by the judges that act in the four branches of the Jury Court of the capital to apply the qualifier. Among the main results of the study, the following stand out: i) the SJC has been slow to investigate, prosecute and prosecute the murders of women; ii) the feminicide qualifier is no longer applied even in cases where the accused were men with whom the victims had a family or affectionate relationship; iii) the procedural instruction phase is not used to identify elements that can help in the application of the qualifier; and iv) the racial profiling of victims is completely ignored. Such findings point to the need to train SJC agents. Finally, looking to the future, the present academic study encourages thinking about alternatives to face Femicide away from the punitive power, while making recommendations to the Policy to Combat Violence against Women in Pernambuco, aiming to avoid revictimization and prevent re-victimization. occurrence of the crime.